LITERATURE REVIEW: PERANAN ACAULOSPORA TERHADAP PENYERAPAN FOSFOR PADA AKAR TANAMAN SINGKONG - Khastini, Rida Oktorida; Avilia, Alma; Salsabila, Nuriana; Febrianty, Rafiony Eka; Aisy, Rihadatul; Frandista, Saniyyah Cinta (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Mycorrhiza is a form of mutualistic symbiosis between plant roots (rhiza) and fungi (mykes). Plants will get various kinds of nutrients, especially phosphorus (P) from their mycorrhiza, while mycorrhiza will get carbon (C) from plants. Phosphorus is a macro nutrient that plants must have. Phosphorus has important functions in plants, namely during respiration, photosynthesis, energy transport, energy storage, cell enlargement, cell division, as well as processes within plants, stimulating plant root development and germination. Mycorrhiza is grouped into three types, namely ectendomycorrhiza, ectomycorrhiza, and endomycorrhiza. This journal review uses the SLR or Systematic Literature Review method with the aim of knowing the meaning of mycorrhiza, characteristics, enzymes that play a role, the mechanism of phosphorus absorption in mycorrhiza, mycorrhizal colonization, and mycorrhizal symbiosis in cassava plants. This article discusses mycorrhiza, one of the mycorrhizal genera, namely Acaulospora, which is included in the endomycorrhiza or Vesicular Arbuscular Mycorrhiza (VAM). The spores are characterized by a brownish yellow color and a rough surface like orange peel. The phosphatase enzyme is produced by Acaulospora hyphae. This enzyme helps increase the amount of P nutrients that are useful for plants by releasing the fixation of P nutrients from Al, Fe, and Ca in the soil, so that phosphate elements are available to plants.